Description of the larva of Cinygmula levanidovi Tshernova & Belov, 1982(Ephemeroptera, Heptageniidae) with redescription of the male adult from the Russian Far East - Tiunova, Tatiana M. (Zootaxa, 2020)
The larvae, male and female imagines, and eggs of Cinygmula levanidovi Tshernova & Belov 1982 are described based on reared specimens from the Russian Far East. The larvae, female imago and eggs are described and illustrated for the first time. The larva of C. levanidovi is similar to the one of C. hirasana Imanishi, 1935 and C. kurenzovi (Bajkova, 1965). However, it can be distinguished from these species and from all other Far Eastern Cinygmula by the shape of its tergalius I, which has a heart-shape and bears a single short gill filament. Tergalius I of C. hirasana and C. kurenzovi possess a similar shape, but there are no gill filaments on the first and the other tergalii.